Pengaruh Modul Elektronik Terhadap Ketrampilan Menulis Puisi Pada Siswa Kelas VIII di SMP Negeri 4 Muncar - Ulya Nurul Laili; Vella Citra Veronika; Hermanto Hermanto (Jurnal Pendidikan dan Pembelajaran, 2022)
Poetry writing skills are one of the materials that require students to be able to present their written work. Based on the results of observations and interviews at SMP Negeri 4 Muncar, it was found that the eighth grade students had difficulties in writing poetry. Students tend not to be able to distinguish the vocabulary used in poetry and descriptive texts, so that students' work tends to lead to descriptive texts. One of them is the use of inappropriate learning media which affects the limited knowledge of students. In the learning process at SMP Negeri 4 Muncar using print media, namely package books. The use of this textbook is considered less effective in delivering the material, because students do not get real examples of the poem. Therefore, researchers use electronic modules as learning media. This research uses quantitative research with a quasi-experimental design. The samples of this study were students of class VIII B as the experimental class and VIII C as the control class. The data in this study were obtained from the results of the pre-test and post-test of the experimental class and the control class. Data analysis in this study used the SPSS 26.0.0 application. This study aims to measure the effect of using electronic modules on poetry writing skills and to determine the differences in poetry writing skills using electronic modules. Based on the value of the pre-test results of the experimental class, the average value was 62.44 and the average value of the post-test results was 84.26. While the results of hypothesis testing are known to be sig.(2tailed) < 0.000 <0.05, there is an effect of using electronic modules on poetry writing skills in class VIII students of SMP Negeri 4 Muncar.